Pemberdayaan Masyarakat Desa Kedungwungu melalui Sosialisasi dan Pelatihan Kerajinan Tangan dari Limbah Jerami - Amalia, Eka Nurul; Farcha, Iddiya; Anggraini, Devy Dwi; Fatmawati, Fatmawati; Akrom, Luqi Zidan Shofi; Ibadillah, M. Nashuikhul; Sari, Putri Nabela Sintiya; Putri, Resti Astuti Misatun; Rizka Ulima Qotrunnida; Rizki Nur Wijayanti; Vicky Mailani Widya Astuty; Zunita Zahrotur Rohmah; Ahmad Febrizan; Andni, Riyan; Kirom, Cihwanul; Noor, Sufiana (Universitas Methodist Indonesia, 2024)
Kedungwungu Village is one of the villages with prime commodities in the form of rice agricultural products. The existence of rice farming products has a positive impact on economic growth in Kedungwungu Village. However, the boom in rice farming also hurts society. Straw waste which is the result of rice farming is not utilized by the people of Kedungwungu Village. The people of Kedungwungu Village prefer to burn or leave straw waste next to the rice fields. Accumulating straw waste can pollute the environment and even cause various diseases. Meanwhile, burning straw waste can hurt human health and pollute the air. Based on these problems, outreach, and training on straw crafts were carried out to minimize the non-utilization of straw waste by the people of Kedungwungu Village. There are two sessions, namely a socialization session and a training session. The outreach session aims to provide public understanding of the dangers of not utilizing straw waste from various aspects of life. Meanwhile, the training session provided the public with an understanding of the use of straw waste in more useful items, namely straw crafts. This activity involved members of the Kedungwungu Village PKK as participants. From this activity, it was found that the participants were happy with the activities carried out because they could provide insight into the negative impacts of not utilizing straw waste and how to use it. Participants also explained that with this activity they also gained knowledge about making crafts from straw waste which adds functional value and economic value.